Fabrication, property and performance evaluation of Stainless Steel 430L as porous supports for metal supported solid oxide fuel cells - Fu, Shengjie; Zhang, Jinqiu; Xu, Kai; Yang, Jun; Zhu, Liangzhu (Frontiers in Energy Research, 2023)
Metal-supported solid oxide fuel cells (MS-SOFCs) have attracted increasing attention due to their superior mechanical strength, relatively low material cost, and capability of fast thermal cycling, as compared to the conventional all-ceramic solid oxide fuel cell. However, fabrication of MS-SOFCs still remains challenging. This study reports a cost-effective powder metallurgical manufacturing route for producing MS-SOFCs. Stainless steel 430L (SS430L) powder is selected for producing the metal support due to its relatively low cost and good thermal expansion compatibility. MS-SOFC button cells with the SS430L/YSZ|Ni/YSZ|YSZ|LSCF structure were successfully prepared by co-sintering and ultrasonic pyrolytic spraying. We found that the trace oxygen level in the dilute H2/Ar gas mixture could play a drastic role in laboratory sintering of the SS430L support; local oxygen control is essential, particularly to avoid Cr oxidation. The addition of no more than 10% YSZ as a second phase to SS430L substantially minimized over-sintering of the SS430L support, leading to a more porous metallic-type substrate, while the electrical conductivity and thermal expansion were not much affected. The fabricated MS-SOFC button cells with the SS430L/YSZ|Ni/YSZ|YSZ|LSCF structure delivered a maximum power density of 180 mW cm-2 at 800°C with an open-circuit voltage of 1.13 V, using dry hydrogen as the fuel and ambient air as an oxidant. A cell tested at 750°C showed relatively good stability for a period of 140 h. While the performance still needs further optimization, the high OCV and good stability indicated that the reported powder metallurgy route is a promising method, and the relevant experimental details, particularly on producing metallic and oxidation-free porous supports, are critical for the preparation of MS-SOFCs.